Peran Akademisi Untuk Penguatan Akses Pangan Masyarakat Dalam Rangka Revitasisasi Agribisnis - Sibuea, Muhammad Buchari (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Agricultural development will essentially boils down to how providing the food evenly in all of society, which are easily affordable, guaranteed low prices with a continous nutrient. Although it is recognized that food also is a commercial commodity, but in the context of food security oriented aspect of community food remains a top priority. Agribusiness revitalization are therefore is the best thing to do in strengthening community food access. But if possible, efforts should be made a breakthrough expansion of domestic and foreign markets to is supported goodwill from any party related directly or indirectly with food, especially from among the agricultural colleges, departements and non-departemental agencies, local governments, social agencies and the farming community itself, when it runs harmonious and sustainable, in turn, will provide optimal result and the best for the nation and the country of Indonesia. Innovation and competence are generated by the agricultural higher education, will be meaning ful if it can be implemented well inthe whole of the farmers with the support of relevant institutions with integrated and sustainable manner.Keyword : Food Access, Agribusiness Revitalization.